Hybrid layer-by-layer assembly of AuNPs/NSF composite for electrochemical detection of miRNA-196a - Jun Ji; Gaofan Shi; Jiayi Jiang; Shu Wu; Haoyuan Su; Hongzhi Pan; Dongdong Zeng (Discover Nano)
Abstract Detection of microRNA-196a (miRNA-196a) is crucial in cancer research, enabling early diagnosis and providing guidance for individualized treatment. In this work, we employed a naturally occurring negatively charged nano silk fibroin (NSF) with high mechanical properties, biocompatibility, and conductivity to be encapsulated with a positively charged gold nanoparticles (AuNPs) were used as film-forming materials for electrostatic layer-by-layer self-assembly to modify the working electrode of the screen-printed carbon electrode (SPCE). Under the optimized experimental conditions, the uniformly distributed AuNPs on the surface of the multilayer film modified SPCE (AuNPs/NSF)5.5/SPCE combined with the sulfhydryl-modified capture probe cp-DNA through gold-sulfur bonds. Furthermore, miRNA-196a is specifically captured through complementary base pairing to achieve highly sensitive and specific detection. (AuNPs/NSF)5.5/SPCE electrode can detect miRNA-196a in a concentration range of 1.0 × 10−13 to 1.0 × 10−6 M, and the calculated detection limit is 4.63 × 10−14 M when the signal-to-noise ratio is 3. The obtained results showed that the (AuNPs/NSF)5.5/SPCE has excellent selectivity and good stability over time.